Assessment of Arsenic in Groundwater in Monguno, Borno State, Nigeria - Umar, I. M.; Sheriff, B. M.; Muhammad, B. B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
Arsenic contamination poses a severe health threat in the semi-arid region of North-eastern Nigeria, particularly in Monguno town, Borno State. This study rigorously evaluated groundwater arsenic concentrations in 102 samples from various boreholes across Upper, Middle, and Lower aquifers of the Chad Formation, utilizing the Palintest Digital Arsenator Test Kit. To ensure precision, each water sample underwent analysis twice, totaling 204 tested and analyzed samples. Furthermore, the geographical coordinates of the 102 boreholes were meticulously mapped using QGIS (Quantum Geographic Information System), providing a visual representation and analysis of the arsenic presence. Findings revealed that only 3 samples met the WHO recommended threshold, 56 fell within the 10-50 µg/L range, signifying a low risk, while 43 samples exceeded 50 µg/L, breaching safety limits. Prolonged exposure to high arsenic levels can lead to severe health implications. A comprehensive human health risk assessment considered parameters such as Average Daily Dose (ADD), Hazard Quotient (HQ), and Cancer Risk (CR). Notably, for 43 water sources with arsenic concentrations exceeding 50 µg/L, Hazard Quotient (HQ) values ranged from 1.2 to 5.3, indicating potential health risks. These elevated values underscore potential carcinogenic and non-carcinogenic hazards in Monguno. A direct linear relationship was observed between HQ and arsenic concentrations across all samples, reinforcing the correlation. Despite the absence of specific reference values for Monguno, the analogous trend in North Central Nigeria reinforces this observation. Urgent collaborative efforts are imperative for intervention and remediation, emphasizing the need for cooperation between government agencies, non-governmental organizations, research institutions, and the local community. Continuous research and monitoring are vital to understanding arsenic sources and distribution, ensuring the long-term effectiveness of remediation measures, and securing safe drinking water access for the community.